Hubungan Efikasi Diri, Kepatuhan dan Dukungan Keluarga Dengan Manajemen Diri Penderita Diabetes Mellitus Tipe 2 di Surabaya - Ach. Arfan Adinata; Minarti Minarti; Kastubi Kastubi (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
Introduction: Diabetes care is complex, requiring long-term care and support. Diabetics face challenges in managing themselves by making the right decisions every day, so people with diabetes mellitus often experience decreased motivation, hopelessness decreased capacity to manage diabetes and, difficulty reducing habits or routines that take. Objectives: The purpose of this study was to identify the relationship of self-efficacy, compliance and family support with self-management of people with DMT2. Methods: The design of this study is a cross-sectional approach. The relationship between one and several variables is expressed by the magnitude of the correlation coefficient and statistical significance. The research population was 165 people, the sample size based on Isaac & Michael's table with an error rate of 10% was 103 respondents. The sampling technique is done by non-probability sampling that is purposive sampling. Results: The results showed that there was a significant relationship between self-efficacy (P-Value 0.042), compliance (P-Value 0.001) and family support (P-Value 0.035), with self-management. Conclusions: Based on the results of the study, it can be concluded that in this study self-management of patients with type 2 diabetes mellitus was associated with self-efficacy, compliance and family support. DMT2 sufferers who have good self-efficacy will help them in managing self-management well, as well as compliant DMT2 patients will also have good self-management. Good family support for people with DMT2 will have a good impact on their self-management.